Pengarahan Teknik Pemasaran Dengan Sosial Media Dalam Upaya Pengenalan Digital Marketing - Tutri Indraswari; Kartika Sari Dewi; Ita Darsita (Universitas Pamulang, 2022)
This Community Service activity aims to provide Marketing Techniques Directions with Social Media in an effort to introduce digital marketing to members of the Asri Berseri Waste Bank, Pamulang, South Tangerang. The method of activity used is to provide explanations and directions on how and steps to use social media properly. After being analyzed, we gave an explanation to the participants about how to use social media as a marketing technique and the introduction of technology in marketing products in today's digital marketing era. PKM activities play a positive role in increasing knowledge and hope to be better at using existing social media, in order to increase household income